Microencapsulation of Sacha Inchi (Plukenetia huayllabambana) Oil by Spray Drying with Camu Camu (Myrciaria dubia (H.B.K.) Mc Vaugh) and Mango (Mangifera indica) Skins - Alarcón Rivera, Rafael (2020)
Indexado en DOAJ